The Effect of Adding Moringa Leaf Powder (Moringa oleifera) on the Chemical Content of Chicken Nuggets - Aristika, Gega Indah; Riwu, Agustinus Rudolf; Sulmiyati, Sulmiyati (Universitas Bengkulu, 2024)
Moringa leaves contain high nutrients and some saponins play a role in lowering cholesterol levels. The use of Moringa leaves in chicken nuggets is becoming an innovation to produce functional food products. This research aimed to analyze the effect of the mixed-use of Moringa leaf powder (Moringa oleifera) on the chemical content of chicken nuggets. The research design is completely randomized, with four treatments and four replications. The treatments in this research were the level of addition of Moringa leaf powder, Treatment K0=0% (control); K1= 10%, K2=20%, and K3=30%. The results of statistical analysis showed an effect of significant (P<0.01) on crude protein, crude fat, crude fiber, and cholesterol content on chicken nuggets. The conclusion is that the addition of 10-30% Moringa leaf powder reduces the crude protein content, crude fat content, and cholesterol content and can increase the crude fiber content.